2013
DOI: 10.1097/wnr.0b013e3283625b5b
|View full text |Cite
|
Sign up to set email alerts
|

Benevolent sexism alters executive brain responses

Abstract: Benevolence is widespread in our societies. It is defined as considering a subordinate group nicely but condescendingly, that is, with charity. Deleterious consequences for the target have been reported in the literature. In this experiment, we used functional MRI (fMRI) to identify whether being the target of (sexist) benevolence induces changes in brain activity associated with a working memory task. Participants were confronted by benevolent, hostile, or neutral comments before and while performing a readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Women exposed to hostilely sexist treatment in the workplace experience lower job satisfaction and increased absenteeism, depression, and physical illness symptoms (Fitzgerald, ). Exposure to benevolently sexist treatment increases women's rumination, reduces their working memory capacity (Dardenne et al., ; Dardenne, Dumont, & Bollier, ), and negatively predicts their grade‐point average and self‐efficacy in college science, technology, engineering, and mathematics (STEM) classes (Kuchynka et al., ).…”
Section: System Justification Theory and Zero‐sum Thinkingmentioning
confidence: 99%
“…Women exposed to hostilely sexist treatment in the workplace experience lower job satisfaction and increased absenteeism, depression, and physical illness symptoms (Fitzgerald, ). Exposure to benevolently sexist treatment increases women's rumination, reduces their working memory capacity (Dardenne et al., ; Dardenne, Dumont, & Bollier, ), and negatively predicts their grade‐point average and self‐efficacy in college science, technology, engineering, and mathematics (STEM) classes (Kuchynka et al., ).…”
Section: System Justification Theory and Zero‐sum Thinkingmentioning
confidence: 99%
“…In contrast, exposure to benevolent sexism elicits a different set of responses including self-objectification, body shame (Calogero & Jost, 2011), and prolonged cardiovascular recovery (Salomon et al, 2015). Benevolent sexism also impairs women’s cognitive performance more than hostile sexism does (Dardenne, Dumont, & Bollier, 2007; Vescio, Gervais, Snyder, & Hoover, 2005) because it reduces working memory capacity by increasing intrusive thoughts about incompetence and by eliciting attempts to suppress these thoughts (Dardenne et al, 2007; Dardenne et al, 2013).…”
Section: Ambivalent Sexism Theorymentioning
confidence: 99%
“…Several authors have precisely shown that the negative expectancy induced by social representations is most likely to impact tasks that tap the most into executive processes, i.e. high-level cognitive processes which permit regulation during goal-directed actions ( Croizet et al, 2004 ; Dardenne et al, 2013 ; Schmader & Johns, 2003 ; Schmader, Johns, & Forbes, 2008 ).…”
Section: Introductionmentioning
confidence: 99%